Digital Fame, Ecological Fragility: Strategic Management of Trend-Driven Volcanic Tourism - Astrid Apriliana; Haniek Listyorini (Politeknik Negeri Bandung, 2026)
Social media-induced tourism triggers rapid visitor surges that often outpace destination management capacity. This study examines Kalitalang Ecotourism on Mount Merapi's slopes, where